Direct Investigation of the Birefringent Optical Properties of Black Phosphorus with Picosecond Interferometry. Issue 1 (29th November 2017) - Zheng, Wei; Nemilentsau, Andrei; Lattery, Dustin; Wang, Peipei; Low, Tony; Zhu, Jie; Wang, Xiaojia
Abstract: Black phosphorus (BP) is an emerging 2D semiconducting material with great potential for nanoelectronic and nanophotonic applications, especially owing to its unique anisotropic electrical and optical properties. Many theoretical studies have predicted the anisotropic optical properties of BP, but the direct experimental quantification remains challenging. The difficulties stem from the ease of BP's degradation when exposed to air in ambient conditions, and from the indirect nature of conventional approaches that are subject to large measurement uncertainties. This work reports a direct investigation of the birefringent optical constants of micrometer‐thick BP samples with picosecond (ps) interferometry, over the wavelength range from 780 to 890 nm. In this ps‐interferometry approach, an ultrathin (5 nm) platinum layer for launching acoustic waves naturally protects the BP flake from degradation. The birefringent optical constants of BP for light polarization along the two primary crystalline orientations, zigzag and armchair, are directly obtained via fitting the attenuated Brillouin scattering signals. A biexponential model is further proposed to analyze the Brillouin scattering signals for a random incident light polarization. The BP experimental results and the associated measurement sensitivity analysis demonstrate the reliability and accuracy of the ps‐interferometry approach for capturing the polarization‐dependent optical properties of birefringent materials. Abstract : Black phosphorus (BP) is an emerging 2D semiconducting material with unique anisotropic optical properties. This work reports a direct investigation of the birefringent optical constants of BP with picosecond‐interferometry in the near‐infrared regime. The birefringent optical constants of BP for light polarization along zigzag and armchair directions are obtained via analyzing the attenuated Brillouin scattering signals.